Correlation of Ultrasonography Parameters with Tissue Transglutaminase Antibody Assay in the Diagnosis of Childhood Celiac Disease - Maralakunte, Muniraju; Debi, Uma; Singh, Lokesh; Prasad, Kaushal Kishor; Lal, Sadhna B; Rehman, Tanveer (Archives of Clinical and Medical Case Reports, 2020)
Objective: The present study aimed to evaluate the potential benefits of ultrasonographic (USG) assessment in the diagnostic workup of children suspected of having celiac disease and its correlation with tissue transglutaminase (TTG) antibody assay. Materials and methods: A retro-prospective study, consisting 30 children with biopsy proven celiac disease diagnosis, was conducted. The tissue transglutaminase (tTG) assay was done on all the children, and further the children were subclassified based on the tTG titer values. The transabdominal sonography using convex (3-5 MHz) and linear (7-12 MHz) ultrasound probes was carried on the subjects, assessing the bowel lumen dimeter, bowel wall thickness, abnormal rugal folds count, presence of perihepatic fluid, fatty hepatic changes and mesenteric lymphadenopathy. Routine abdominal sonography was also carried out to complete the detailed evaluation of the abdomen. The sonographic bowel findings and the different classes of the tTG titers were correlated. Results: The median (IQR) age at onset of symptoms and at diagnosis was 6 (4-9) years. The median (IQR) value of blood tissue transglutaminase level (tTG) was 535 U/mL (63-7100), and most of the children belonged to class A (n=18, 60%) subclassification followed by class C (n=7, 23.3%) and class B (n=5, 16.6%). On sonological evaluation, the bowel abnormalities including bowel thickening was seen in 8 (26.6%) of the children, followed by the reduced jejunal folds and transient intussusception in the same frequency (n=5, 16.6%) and, hyper-peristalsis in 4 (13.3%) children. No dilated bowel loops were seen. Extra-intestinal observations like fatty liver changes, mesenteric lymphadenopathy, and peritoneal free fluid were noted in 23 (76.6%), 6 (20%), and 4 (13.3%) of the children respectively. Conclusion: Ultrasound is the most widely u